EMPLOYEE PERFORMANCE: THE ROLE OF MOTIVATION IN LEADERSHIP AND WORK STRESS - Usman, Usman; Nurhadi, Ilham (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the role of leadership and work stress on work motivation and employee performance at the Muna District Attorney’s Office, while also testing the mediating role of work motivation. The study employed a quantitative approach involving 40 employees as research respondents. Data were collected through questionnaire distribution developed based on indicators relevant to the research variables. Path analysis was conducted using the SmartPLS application. The results indicate that leadership does not have a significant effect on either work motivation or employee performance. In contrast, work stress has a significant effect on both work motivation and employee performance. Furthermore, work motivation significantly influences employee performance. The findings also reveal that work motivation mediates the relationship between leadership and work stress with employee performance. Therefore, work motivation plays a strategic role in enhancing employee performance within the Muna District Attorney’s Office.